The Impact of Globalization on Local Economic Development: Challenges and Opportunities - Muhammad Fidiandri Putra; Pudji Astuty (Jurnal Multidisiplin Indonesia, 2025)
This research examines the impact of globalization on local economic development in Indonesia, focusing on challenges and opportunities that emerge in an increasingly integrated global economy. Through a qualitative approach using literature review and secondary data analysis, this study identifies that globalization has resulted in increased competition for local producers, dependence on external markets, and pressure on traditional industries. However, globalization also opens access to broader markets, facilitates technology and knowledge transfer, and creates foreign investment opportunities. The research finds that regions with adaptive policies and strong institutional capacity are better able to capitalize on globalization opportunities while minimizing negative impacts. The findings highlight the importance of integrated development strategies between national policies and local initiatives to optimize the benefits of globalization for local economies.